PERHITUNGAN NORMALISASI DATA MENGGUNAKAN METODE LEVERETT J-FUNCTION UNTUK HASIL UJI TEKANAN KAPILER DENGAN ALAT SENTRIFUGAL PADA BATUAN - Aly Rasyid; Abdullah Rizky Agusman; Nona Julia Zalfa Nisrina (Jurnal Bhara Petro Energi, 2026)
This study discusses the application of the Leverett J-Function method in the process of normalizing capillary pressure (Pc) data from SCAL tests on centrifuges in reservoir rocks to obtain more accurate rock characteristics, and focuses on understanding the relationship between capillary pressure, water saturation, porosity, and permeability which play an important role in determining fluid distribution and flow quality in reservoir rocks. The focus of this study is directed at assessing the relationship between Pc and Sw, grouping rock characteristics using the Hydraulic Flow Unit (HFU) method, and applying Leverett J-Function to normalize data so that measurement results from various samples can be compared consistently. The results show that rocks can be grouped into three HFUs with varying flow quality, where HFU 1 shows the best quality, HFU 2 represents medium flow, and HFU 3 has low quality. Normalization using Leverett J-Function successfully unifies capillary pressure data into a more uniform curve, while the denormalization results provide a more realistic picture of reservoir conditions. The combination of HFU and Leverett J-Function methods has proven effective in improving the accuracy of petrophysical interpretations and supporting oil and gas reservoir management.